1978
DOI: 10.1530/jrf.0.0520009
|View full text |Cite
|
Sign up to set email alerts
|

Serum oestrogen, progesterone and prolactin concentrations in cyclic, pregnant and lactating beagle dogs

Abstract: Summary. No correlations between the three hormones measured were found in any of the reproductive states examined. In 2 out of 8 dogs a negative correlation between serum progesterone and prolactin levels was found at Day 11 and Day 15, respectively (Day 0 = first day of copulation). In all of the 8 animals in which the progesterone and prolactin concentrations were measured in the same samples in late pregnancy, a negatively correlated overall pattern was obtained between both hormone profiles. No correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1
3

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 15 publications
3
20
1
3
Order By: Relevance
“…Moller (1973) describes a resemblance between the profiles of progesterone secretion in pseudopregnant and pregnant blue fox females but does not comment on the persistence of corpora lutea in this species. In the bitch also, similar progesterone secretion profiles in pregnancy and pseudopregnancy have been observed by Smith & McDonald (1974), Hadley (1975) and Graf (1978). Smith Previous work has demonstrated that pituitary secretions are involved in the persistence of the corpora lutea in the red fox (Bonnin-Laffargue et al, 1972).…”
Section: Methodssupporting
confidence: 55%
See 4 more Smart Citations
“…Moller (1973) describes a resemblance between the profiles of progesterone secretion in pseudopregnant and pregnant blue fox females but does not comment on the persistence of corpora lutea in this species. In the bitch also, similar progesterone secretion profiles in pregnancy and pseudopregnancy have been observed by Smith & McDonald (1974), Hadley (1975) and Graf (1978). Smith Previous work has demonstrated that pituitary secretions are involved in the persistence of the corpora lutea in the red fox (Bonnin-Laffargue et al, 1972).…”
Section: Methodssupporting
confidence: 55%
“…Hadley (1975) also failed to observe the fall in progesterone concentrations after oestrus and subsequent large rise to peak gestational levels 19-24 days after the first day of oestrus which was described by Smith & McDonald (1974). Graf (1978) has confirmed the observations of Smith & McDonald (1974) and suggested an extra-ovarian source of progesterone for the second increase in serum progesterone concentration observed, which coincides with the time of implantatio'n. We have been unable to clarify the question of whether the corpus luteum is the major site of progesterone production in the red fox.…”
Section: Methodssupporting
confidence: 53%
See 3 more Smart Citations